Belajar Matematika dalam Perspektif Islam - Imamuddin, M.; Isnaniah, Isnaniah; Januar, Januar; Hadini, Hadini; Andryadi, Andryadi; M., Zaharuddin; Susanti, Weti (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2025)
This study examines the importance of learning mathematics from an Islamic perspective, arguing thatthis discipline is not only a cognitive tool, but also a spiritual means of understanding the greatness ofAllah SWT. In Islam, mathematics has a unique position as the Qur’an implicitly refers to order, balanceand careful calculation in the creation of the universe, as seen in the movement of celestial bodies or thedivision of inheritance. Hadiths of the Prophet Muhammad also encourage the pursuit of knowledge andthe use of reason, which broadly includes the study of mathematics as a foundation for the advancementof science. Through the library research method, the researcher collected and analyzed various literaturesources, including journal articles, academic books, books of tafsir, and Hadith, both in digital and printformats. To ensure validity and depth of analysis, the researcher applied data triangulation, comparing andconfirming findings from various sources. The results of the analysis show that learning mathematics canfoster tafakur (contemplation) and tadabbur (deep appreciation) of Allah’s creation, thus increasing faith andpiety. The study concludes that mathematics, from an Islamic perspective, is a way to uncover the secrets ofthe universe and witness the signs of divine power, making it a worshipful activity with a spiritual dimension.